Predictive Factors of Abiraterone Response in Patients With High-Risk Metastatic Hormone-Sensitive Prostate Cancer - Jaeyoung Cho; Jungyo Suh; Dalsan You; In Gab Jeong; Jun Hyuk Hong; Hanjong Ahn; Bumjin Lim (Journal of Urologic Oncology)
Purpose This study aimed to identify predictive factors for the response to abiraterone in patients with high-risk metastatic hormone-sensitive prostate cancer (mHSPC). Materials and Methods This study analyzed the clinical characteristics of 167 patients with high-risk mHSPC who received abiraterone. Univariate and multivariable Cox proportional hazard regression analyses were conducted to identify predictive factors for castration-resistant prostate cancer (CRPC)-free survival and cancer-specific survival. Results The mean age at presentation was 71.62±8.12 years. The prostate-specific antigen level was 218 ng/mL (interquartile range, 70–654 ng/mL). Of the 167 patients, 118 (72%) had a biopsy Gleason grade of 5, 43 patients (28.7%) had CRPC, and 30 patients (18.0%) died after a mean follow-up period of 13.5 months. In the multivariable Cox proportional hazard regression analyses for CRPC-free survival, a Gleason grade of 5 (hazard ratio [HR], 2.888; 95% confidence interval [CI], 1.133–7.361; p=0.026) and bone lesions ≥10 (HR, 4.194; 95% CI, 1.760–9.997; p=0.001) were significantly associated with CRPC-free survival. In the multivariable Cox proportional hazard regression analyses for cancer-specific survival, bone lesions ≥10 (HR, 3.185; 95% CI, 1.215–8.348; p=0.001) was significantly associated with cancer-specific survival. Conclusions Patients with bone lesions ≥10 and Gleason grade of 5 are at higher risk of developing CRPC, and bone lesions ≥10 is at higher risk of cancer-specific survival in high-risk mHSPC treated with abiraterone.